THE MODEL OF TOP-DOWN POLICY IMPLEMENTATION IN PNPM MANDIRI URBAN IN PAREPARE SOUTH SULAWESI - Suratman,; Ibrahim, Akmal; Fausy, Ali (IJRDO - Journal of Social Science and Humanities Research, 2016)
The implementation of the top down model policy especially the Meter and Horn policy is not effective yet in implementing the Program Nasional Pemberdayaan Masyarakat Mandiri Perkotaan (PNPM MP) policy in Parepare. Using qualitative method with a case study, the performance of the PNPM MP  Policy implementation aims at assisting and autotomizing the society using three efforts of development. Infrastructure development has been successful, while economy development in business capitals and social development are not effective yet. The causative factors such as the policy standard, resources, inter-organizational communication, organization characteristics, socioeconomy, and disposition are not optimized yet. Therefore, inter-agencies cooperation is needed so that the PNPM MP policy implementation in Parepare can be effective.